Collaboration Network of Legal Education and Training for Local BEstuurs Orgaan in Local Government Regime - M.A. T. Fitriyah; A.E. E. Mahanani; N. A. Permatasari (Future Science)
This research aims to find a collaboration network model between universities, especially law faculties with local governments to provide legal education and training for local bestuurs orgaan. The research begins with identicitation the implementation of tri dharma in college and then associated it with the implementation of local government . This research using local bestuurs orgaan in the area of Surabaya City and Sidoarjo Regency as the object and using it as sample in this research. This research is part of socio-legal research, which is the law is conceptualized as law as what it is (functioning) in society . the type of the data itself in this research using primary and secondary data. We use several Techniques to collecting the data, some of them are using field observation techniques, direct comunnication techniques, dan documenter study technique. In analyzing the data we using qualitative method. The result of this research is; first, universities, especially the law school has a strategic role to provide legal education and training as manifestation of dharma, in this case the relation with the regime of local government, the universities in each region have a moral obligation to support the implementation of clean and good government in any region they entrusted. Second , the network collaboration model will be achieved through collaboration between universities, especially law faculties with local government, especially in the Regional Civil Service Agency, specifically the Education and Training Section, which is the responsible in human resource development.